Evaluation of the Effect of Long-term Use of Three Intracanal Medicaments on the Radicular Dentin Microhardness and Fracture Resistance: An in vitro study - Ankita Dilip Amonkar; Neha Sunil Dhaded; Preeti Kore Doddwad; Anand C. Patil; Shivayogi M. Hugar; Shilpa Bhandi; A. Thirumal Raj; Shankargouda Patil; Alessio Zanza; Luca Testarelli (University of Zagreb. School of Dental Medicine, 2021)
Objectives: The aim of this research was to evaluate the effect of long-term use of three intracanal medicaments on the radicular dentin microhardness and fracture resistance. Material and methods: A chemomechanical preparation was done using the Protaper rotary instruments up to F3. The teeth were stored in an incubator at 37°C at 100% humidity and were categorized in three groups by random allocation, namely: Triple Antibiotic Paste (TAP), Calcium hydroxide paste (Apexcal) and Ledermix. Following medicament application, the access openings of all teeth were sealed with 4 mm thickness of cavit. The samples were stored for periods of 1 week, 1 month and 3months. Two dentin cylinders measuring 5mm and 3mm were obtained from each sample. The cervical third was used for fracture resistance and the middle third was used for micro hardness evaluation. The microhardness testing was done using a Knoop microhardness tester, and the fracture resistance testing was done using the universal testing machine. Results: Calcium hydroxide showed maximally negative effect on the physical properties of radicular dentin compared to TAP (p= 0.0100 at one month and Ledermix (p=0.0001 at one month ). With an increase in the application time, there was an increased deterioration in the physical properties of radicular dentin. Conclusion: Long-term placement of calcium hydroxide, Triple Antibiotic Paste, and Ledermix (p= 0.0001at 3 months) significantly affects the microhardness and fracture resistance of radicular dentin.